(untitled) (Research, Society and Development, 2021)
Objective: To analyze the influenza vaccine coverage in the coastal plain region of the State of Piauí in the period 2015-2020. Methods: This is a descriptive and exploratory research with a quantitative approach. Data were collected through the Information System of the National Immunization Program (SIPNI) and refer to influenza vaccination coverage in the Coastal Plain Region, located in the State of Piauí. It was decided to include four priority groups in the research: children aged 6 months to under 6 years, pregnant women, people over 60 years and health professionals. The collected data were tabulated and analyzed at Microsoft Office Excel software. The results of the descriptive analysis were presented through tables and graphs. Results: It was found that many cities failed to reach the vaccination coverage goal recommended by the Brazilian Ministry of Health. The groups of children and pregnant women obtained the lowest percentages of vaccination. The elderly and health professionals, even not reaching the goal every year, achieved the best percentages of vaccination. Conclusion: It was possible to verify fluctuations in the averages of vaccination coverage in the analyzed audiences, and most of these averages were below the goal set by the Ministry of Health for vaccination coverage of Influenza. In view of this, the importance of evaluating vaccination coverage on an individual basis is emphasized, in order to know the local reality of each city, and thus, plan different actions considering the needs of each region.